Literasi kesehatan ibu dan anak kalangan ibu PKK masyarakat Kecamatan Payakumbuh Timur - Maharani, Defitria; Khadijah, Ute Lies Siti; Saepudin, Encang (Faculty of Communication, Padjadjaran University, 2024)
Maternal and child health is a crucial aspect of public health development, considering the vital role of mothers as primary caregivers and the foundation of the family. The rapid advancement of science and technology (IPTEK) today is unavoidable, and the need for information has become a primary necessity for humans. To live in an information society, knowledge and information management techniques are required. An individual's ability to access, understand, and use information and health services to make informed decisions is known as health information literacy. Health information literacy is crucial in building a quality society, particularly concerning maternal and child health. This study aims to assess the ability of the community to access and understand information regarding maternal and child health in Payakumbuh Timur District, specifically among the mothers of the Family Welfare Empowerment (PKK) group. This research employs a quantitative method with a descriptive survey approach utilizing questionnaires, observations, and interviews for data collection. The study results show that the community's ability in maternal and child health information literacy is categorized as high. Seven information literacy skills were measured, all of which were rated high: 1. The ability to recognize community information (83.8%), 2. The ability to identify information gaps (82.4%), 3. The ability to develop information search strategies (69.1%), 4. The ability to access information (86.8%), 5. The ability to evaluate information (70.6%), 6. The ability to manage information (89.7%), and 7. The ability to present information (69.1%). In conclusion, maternal and child health information literacy among PKK mothers in Payakumbuh Timur District is very good, enabling them to effectively access, understand, and use health information to improve family health and well-being.